"A Shooting Star of Conservatism": George S. Benson, the National Education Program and the "Radical Right". (4th December 2017) - MAXWELL, ROBBIE
Abstract : This article reassesses the so-called "Radical Right, " a political phenomenon that emerged in the early 1960s and was especially associated with a controversial conservative anticommunism. The article argues that the National Education Program (NEP), which was founded in Arkansas in 1943, made an important and unheralded contribution to the Radical Right and the consequential activism it stimulated in pockets of the South and Southwest. The article also, however, argues that the Radical Right ultimately made a less significant contribution to the subsequent resurgence of conservatism than has often been suggested. Conventional wisdom maintains that it aligned religious, economic, and racial concerns under the umbrella of anticommunism and thereby fostered a distinctly modern conservatism; the NEP demonstrates that these concerns were not as disparate or marginal prior to the 1960s as this narrative assumes. The Radical Right's fixation with communist subversion also often diluted efforts to promote conservative principles – the NEP became less focussed on advancing ideological principles during this period. After the mid-1950s, moreover, the declining legitimacy of McCarthyite politics outwith parts of the South and Southwest undermined the NEP's wider efforts, precipitated the organization's terminal decline, and ensured that the Radical Right created problems for the broader conservative movement.